Effects of housing conditions on health and gut microbiome of female cynomolgus monkeys and improvement of welfare by checking menstruation under socially housed condition - Yunpeng Yang; Yong Lu; Changshan Gao; Yanhong Nie; Hongfei Wang; Yufei Huang; Haiyan Dong; Qiang Sun (Heliyon)
Laboratory non-human primates (NHPs) are commonly subjected to social deprivation in various scientific researches. However, the impact of social deprivation on gut microbiome remains largely unknown. We examined the health status and gut microbiota of female cynomolgus monkeys housed in isolation or social conditions and found that social deprivation brought adverse effects to monkeys by inhibiting their growth, remodeling the immune status, and decreasing the level of beneficial biochemical parameters. 16S rRNA gene sequencing revealed that the gut microbial composition and function differed between grouped and isolated monkeys. Specifically, grouping the single-caged young monkeys to socially housed condition could decrease the relative abundance of Firmicutes and increase the relative abundance of Bacteroidetes, while separating the socially housed middle-aged monkeys into single cages showed the opposite trend. Besides, training female monkeys to detect menstruation under socially-housed condition could increase their body weight change and adjusting their immune status, thus attenuating the adverse effects of separating them to single cages. Our results verified the significant role of grouping in mitigating adverse health and microbiota alterations caused by isolation in female cynomolgus monkeys and emphasized the importance of training NHPs to cooperate with experimental procedures under socially housed condition, which could not only improve the welfare of cynomolgus monkeys but also enhance the accuracy and reliability of scientific results.